2022
DOI: 10.1186/s12978-022-01450-6
|View full text |Cite
|
Sign up to set email alerts
|

The current situation and future directions for the study on time-to-pregnancy: a scoping review

Abstract: Introduction As problems associated with infertility and population aging increase, there is a growing interest in the factors that cause a decline in human fertility. Time-to-pregnancy (TTP) is a good indicator with which to reflect human fecundability. Here, we present a comprehensive overview of this topic. Methods Relevant qualitative and quantitative studies were identified by searching the Web of science and PubMed electronic databases. We in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 85 publications
1
3
0
Order By: Relevance
“…Based on the results of MS-based proteomics analysis and determination of pyruvate levels, this study confirmed that plasma proteins are beneficial in predicting low fecundability. According to previous studies, women with longer time-to-pregnancy (TTP) have difficulty in conceiving . Our study revealed that the plasma expression levels of PKM, ALDH2, ALDOC, IDH3A, DLST, ER, GAPDH, and pyruvate were significantly lower in infertile women than in women with a shorter TTP who have a greater likelihood of conceiving.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Based on the results of MS-based proteomics analysis and determination of pyruvate levels, this study confirmed that plasma proteins are beneficial in predicting low fecundability. According to previous studies, women with longer time-to-pregnancy (TTP) have difficulty in conceiving . Our study revealed that the plasma expression levels of PKM, ALDH2, ALDOC, IDH3A, DLST, ER, GAPDH, and pyruvate were significantly lower in infertile women than in women with a shorter TTP who have a greater likelihood of conceiving.…”
Section: Discussionsupporting
confidence: 46%
“…According to previous studies, women with longer time-to-pregnancy (TTP) have difficulty in conceiving. 15 Our study revealed that the plasma expression levels of PKM, ALDH2, ALDOC, IDH3A, DLST, ER, GAPDH, and pyruvate were significantly lower in infertile women than in women with a shorter TTP who have a greater likelihood of conceiving. Thus, the downregulation of these proteins indicates a poor pregnancy potential.…”
Section: Discussionmentioning
confidence: 51%
“…All of the women reported they did not smoke. This information was potentially associated with female fecundability 19 and were therefore selected as confounding factors in our study.…”
Section: Methodsmentioning
confidence: 99%
“…Male fecundity can be assessed based on semen quality, testicular volume, and hormonal profiles (Olsen & Ramlau-Hansen, 2014). One measure of couple fecundability is the number of calendar months or menstrual cycles required to conceive, with a longer time-to-pregnancy (TTP) indicating lower fecundity (Hong et al, 2022).…”
Section: Perceived (Sub)fecunditymentioning
confidence: 99%